2021
DOI: 10.1073/pnas.2019251118
|View full text |Cite
|
Sign up to set email alerts
|

The mosquito protein AEG12 displays both cytolytic and antiviral properties via a common lipid transfer mechanism

Abstract: The mosquito protein AEG12 is up-regulated in response to blood meals and flavivirus infection though its function remained elusive. Here, we determine the three-dimensional structure of AEG12 and describe the binding specificity of acyl-chain ligands within its large central hydrophobic cavity. We show that AEG12 displays hemolytic and cytolytic activity by selectively delivering unsaturated fatty acid cargoes into phosphatidylcholine-rich lipid bilayers. This property of AEG12 also enables it to inhibit repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(55 citation statements)
references
References 55 publications
(94 reference statements)
5
50
0
Order By: Relevance
“…This revealed the dramatic temporary increase in the expression of a family of twelve genes containing the insect allergen domain (IPR010629) which are orthologous to the An. gambiae G12 gene and have been found to possess hemolytic, cytolytic, and antiviral properties [60]. We also observed that the family of MBF2 transcription factors -one member of which was previously noted among the highest expressed genes of the anterior midgut (Fig 2C) -surged from just over 1% of the transcriptome to more than 4% at 24 hrs pbm, partially subsiding to approximately 1.7% by 48 hrs pbm.…”
Section: Blood Feeding Initiates a Series Of Transcriptomic Shifts Over The Course Of Digestionsupporting
confidence: 73%
“…This revealed the dramatic temporary increase in the expression of a family of twelve genes containing the insect allergen domain (IPR010629) which are orthologous to the An. gambiae G12 gene and have been found to possess hemolytic, cytolytic, and antiviral properties [60]. We also observed that the family of MBF2 transcription factors -one member of which was previously noted among the highest expressed genes of the anterior midgut (Fig 2C) -surged from just over 1% of the transcriptome to more than 4% at 24 hrs pbm, partially subsiding to approximately 1.7% by 48 hrs pbm.…”
Section: Blood Feeding Initiates a Series Of Transcriptomic Shifts Over The Course Of Digestionsupporting
confidence: 73%
“…This revealed the dramatic temporary increase in the expression of a family of twelve genes containing the insect allergen domain (IPR010629) which are orthologous to the An. gambiae G12 gene and have been found to possess hemolytic, cytolytic, and antiviral properties ( Foo et al, 2021 ). We also observed that the family of MBF2 transcription factors - one member of which was previously noted among the highest expressed genes of the anterior midgut ( Figure 2C ) - surged from just over 1% of the transcriptome to more than 4% at 24 hr pbm, partially subsiding to approximately 1.7% by 48 hr pbm.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that many allergen families are capable of binding lipids and other hydrophobic ligands (113). This activity could allow allergens to perturb biological barriers or deliver immunomodulatory ligands such as bacterial lipids or pollen-associated lipid mediators directly to the immune system, facilitating sensitization (114)(115)(116)(117)(118). However, the presence of lipid ligands or adjuvants could influence both abundance and stability, further contributing to allergenicity.…”
Section: Lipid Ligands As Modulators Of Abundance and Stabilitymentioning
confidence: 99%
“…Other lipid-binding allergens such as Bla g 1 and Bet v 1 could ellicit a similar effect through destabilizing the plasma membrane of epithelial cells. In the case of the former, this is mediated by the delivery of unsaturated fatty acids into biological membranes while the latter is able to insert into a lipid bilayer, presumably disrupting lipid organization and packing ( 114 , 133 ). In this capacity, the lipid-binding abilities of Bet v 1 and Bla g 1 play a dual role in stabilizing their respective ligands while simultaneously contributing to their pro-inflammatory biological functions.…”
Section: Additional Considerations: Biological Activitymentioning
confidence: 99%